Evaluation of Molecular Genetic Diversity and DNA Barcoding of Rita gogra (Family Bagridae) from Narmada River Revealed through Mitochondrial COX1 Gene Sequencing - Garg, R. K.; Dohre, Surbhi (Asian Journal of Biological and Life Sciences)
Background: Since fish have a great deal of variation and phenotypic flexibility, it can occasionally be challenging to identify them just based on morphological features, therefore, various molecular markers are very reliable tools to make identify genetic divergence and differentiations with and between populations. Materials and Methods: The morphological characteristics allowed us to identify the fish as a bagrid catfish. Rita gogra (Skyes 1839), from Narmada River and sent fresh DNA barcode information to the Barcode Life and mitochondrial COX1 gene sequences on GenBank, NCBI, USA with the length of 615 bp (accessions MF687949, MF687950, MH427908, MH427909 and MH427910). Results: Barcoded and NCBI created data showing the highest conserved regions for Rita gogra because it gave more than 99% hits similarities and it differentiated with neighbor species like Rita rita. The average gene polymorphism as haplotype gene diversity was 0.52381 and nucleotide diversity was 0.00473 among three populations indicates good gene diversity of Rita gogra in Narmada River. Genetic differentiation (Gst) was 0.00826, which indicates that highest genetic variation is within populations of Hoshangabad and Mandleshwar and 0.00% was found between Hoshangabad and Maheshwar populations. These results suggest that genetic differentiation among populations of R. gogra is impeded by high gene flow. Conclusion: This research evaluated the efficacy of a COX1 for genetic differentiation and development of barcode for discriminating of fish species encourages the global effort to build a complete library of COX1 sequences associated with specific specimens, which has just started.
Keywords: Gene diversity; Genetic differentiation; Haplotype diversity; Narmada River; Nucleotide diversity